THE LIMITED LIABILITY OF SHAREHOLDERS INDIVIDUAL COMPANY IN LEGAL PERSPECTIVE - Devi Nahrowi (Fakultas Hukum Universitas Islam Indragiri, 2023)
to find out and analyze the status of an individual company and the responsibilities of shareholders of an individual company as a limited liability company, a normative juridical research method with a statutory, conceptual and historical approach. Based on Article 1 point 1, Article 32 of the Company Law 2020 junctis Article 153E of the Company Law 2020, Articles 3 and Article 4, and Article 10 PP 8/2021 and the theoretical theory of fiction, the theory of purposeful wealth, and the theory of corporate organs Individuals qualify as legal entities, and as legal subjects with their own assets separate from the personal assets of the shareholders, and therefore based on Article 153J of the 2020 Company Law the responsibility of the shareholders of an individual company is limited according to the nominal value of the shares they own. The company regulation for micro-small businesses with a single owner as a limited liability company legal entity in the UUPT contains ambiguous norms because a company for micro-small businesses with a single founder can also be established by 2 (two) people as a capital partnership company in the absence of a Commissioner's oversight body can potentially misuse of the company for the personal interests of the Directors and the mixing of the personal assets of the founders and shareholders with the assets of the company as referred to in Article 153J paragraph (2) of the 2020 Company Law.